Effect of various active packaging system on quality and microbial stability of fresh-cut cantaloupe (Cucumis melo L. Var. Reticulates cv. Glamour) - Kamaruddin, Syahidah (2015)
A study was conducted to determine the effect of initial packaging atmosphere by using different packaging system on the quality and microbial stability of fresh-cut Cantaloupe and to investigate the effect of different absorbers. Fresh-cut Cantaloupe was stored in two types of containers; specifically a rigid container and semirigid container. Each of containers was sealed under different conditions. These were Polypropylene (PP) film and Low-Density Polyethylene (LDPE) films. Between the two types of film, Low-Density Polyethylene (LDPE) film material was shown to have better quality of both containers, being the rigid and semirigid containers. It was found that the physico-chemical properties (firmness, colour, total soluble solid, titratable acidity) of fresh-cut Cantaloupe were maintained over 18 days of storage. Meanwhile,for pH value, there are no significant effects in the storage time for all type of packages. Microbial analysis (total plate count and yeast and mould) were found to increase over storage, but LDPE materials were found to have lower TPC compared to the other package. The packages did not exhibit any effects on the YM counts during the 18 days of storage. For the oxygen, carbon dioxide, respiration rate and ethylene production, the LDPE film materials could maintain the quality of about 11 days with acceptable level of oxygen (above 2%) and a moderate level of carbon dioxide (2%-12%). LDPE shows the lowest value of respiration rate and ethylene production in the rigid and semirigid container. The effects of absorbers were investigated after the selection of the seal package materials for rigid and semirigid containers. Two types of absorbers were used namely, oxygen absorber and ethylene absorber. There were four different conditions created in this experiment. The first container does not contain absorber. The second container contained an oxygen absorber. The third container contained ethylene absorber, and finally, the samples included both types of absorbers, being oxygen and ethylene absorbers. It was found that the physicochemical of fresh-cut Cantaloupe (firmness, colour, total soluble solid, titratable acidity) was maintained over 18 days of storage for all types of conditions in an active packaging system. The microbial analysis (total plate count (TPC) and yeast and mould (YM)) were increased throughout the storage time and the storage can last until day 11 for microbial spoilage. It was found that all types of absorbers able to reduce the oxygen concentration of fresh-cut Cantaloupe but too little of oxygen may cause anaerobic metabolism and production of off flavors and odors. The results showed that the absorbers had reduced the oxygen level of oxygen tremendously (below than 2%). The percentage of carbon dioxide had shown the same amount for both containers (2%-12% of CO2). For respiration rate and ethylene production, the ethylene-oxygen absorbers had shown the lowest value for fresh-cut Cantaloupe for both containers. Therefore, the fresh-cut Cantaloupe packaged with LDPE film was found to maintain the quality and microbial stability up to 11 days of postharvest storage for rigid and semirigid container at 2±1°C. The fresh-cut Cantaloupe packaged with LDPE film can be consumed until day 11. However, the package associated with oxygen and ethylene absorbers can be only being consumed up to day 7.